Cardiac troponin testing and the simplified Pulmonary Embolism Severity Index - Spirk, David; Aujesky, Drahomir; Husmann, Marc; Hayoz, Daniel; Baldi, Thomas; Frauchiger, Beat; Banyai, Martin; Baumgartner, Iris; Kucher, Nils (Thrombosis and Haemostasis, 2011)
A low simplified Pulmonary Embolism Severity Index (sPESI), defined as age ≤80 years and absence of systemic hypotension, tachycardia, hypoxia, cancer, heart failure, and lung disease, identifies low-risk patients with acute pulmonary embolism (PE). It is unknown whether cardiac troponin testing improves the prediction of clinical outcomes if the sPESI is not low. In the prospective Swiss Venous Thromboembolism Registry, 369 patients with acute PE and a troponin test (conventional troponin T or I, highly sensitive troponin T) were enrolled from 18 hospitals. A positive test result was defined as a troponin level above the manufacturers assay threshold. Among the 106 (29%) patients with low sPESI, the rate of mortality or PE recurrence at 30 days was 1.0%. Among the 263 (71%) patients with high sPESI, 177 (67%) were troponin-negative and 86 (33%) troponin-positive; the rate of mortality or PE recurrence at 30 days was 4.6% vs. 12.8% (p=0.015), respectively. Overall, risk assessment with a troponin test (hazard ratio [HR] 3.39, 95% confidence interval [CI] 1.38–8.37; p=0.008) maintained its prognostic value for mortality or PE recurrence when adjusted for sPESI (HR 5.80, 95%CI 0.76–44.10; p=0.09). The combination of sPESI with a troponin test resulted in a greater area under the receiver-operating characteristic curve (HR 0.72, 95% CI 0.63–0.81) than sPESI alone (HR 0.63, 95% CI 0.57–0.68) (p=0.023). In conclusion, although cardiac troponin testing may not be required in patients with a low sPESI, it adds prognostic value for early death and recurrence for patients with a high sPESI.
Keywords: Pulmonary embolism; risk stratification; Pulmonary Embolism Severity Index; cardiac troponin